LINGUOCULTURAL FEATURES OF PREDICATION IN RUSSIAN AND UZBEK - Yuldashev Aziz Uzgenovich (Web of Journals Publishing, 2025)
This article deals with the study of linguistic pictures of the world, which are closely related to the study of the problems of interrelation of language and thinking, with the disclosure of national-specific features of language, its ethno-cultural originality.
Keywords: Linguoculturology, syntax, predication, predicate, sentence, utterance, function, syntaxema, linguistics, comparative analysis.